OzoNews Volume XX - 30 October 2020 - United Nations Environment Programme (2021)
In this issue: 1. Kigali Amendment latest ratifications 2. Contingency meeting plans for 2020-2021: update 3. Large ozone hole recorded over Antarctic for 2020, but Montreal Protocol efforts have minimized the damage 4. Operation DEMETER VI thwarts transboundary shipments of illegal waste and ozone depleting substances 5. Linking cooling to climate action and refrigerant phase-down in global environmental agreements 6. Ghana Govt to conserve 465GWh in next decade with introduction of ECOFRIDGES 7. Gambia National Environment Agency trains refrigeration technicians in Upper River Region 8. Special Report: Roadmap for R290 split system air conditioners 9. Conservation and Environment Protection Authority, Customs collaborate on border efforts (Papua New Guinea) 10. Fiji on track to phase-out HCFCS 11. Department of Environment and Natural Resources warns households against use of disinfectants with HFCs (Philippines) 12. India bans split air conditioner imports 13. US EPA protection of stratospheric ozone: Determination 36 for Significant New Alternatives 14. First-of-its-kind Study compares costs of natural & low-GWP refrigerant systems